Improving AI services in Ethiopia - Hoekstra, Dirk (International Livestock Research Institute, 2011)
On 2 and 3 June 2011, the IPMS project organized a workshop: ‘Market-Oriented Smallholder Development: IPMS Experience-Sharing Workshop’. Here, Dirk Hoekstra introduces some promising approaches to the delivery of AI services in rural Ethiopia. This topic is the subject of a special session in the workshop.